Government Efforts to Violate Tapping Box in Malang City Taxpayers - Dian Lovitasari; Durratun Nashihah (University of Merdeka Malang, 2023)
This research describes a tool in assisting the supervisory function of local tax revenues to support the realization of targets on Regional Original Revenue. A device called a tapping box is present in the tax object registered on the local government server to be installed between the cash register and the printer. Every transaction will be recorded on a device that has been connected to the local government server so that when the reporting arrives, the taxpayer only deposits the nominal that has been listed. Although supervision is assisted by technology, local governments also conduct intensive supervision to follow up tax objects that take preventive actions. Various efforts of local governments in expressing and imposing sanctions such as quadruple nominal payments, and so on. The method in this study uses literature reviews sourced from journals and articles. It was found that some tax objects carried out the revocation of tapping boxes, doubling accounts.